...
Пошаговое объяснение:
Уравнение 1:
3*(x-7)-6*(2x+5)=2*(3x-1)+11
3х-21-12х-30=6х-2+11
3х-12х-6х=21+30-2+11
-15х=60
х=60:(-15)
х=-4
Уравнение 2:
-4*(x+5)+6x=22-10x
-4х-20+6х=22-10х
-4х+6х+10х=22+20
12х=42
х=42:12
х=3,5
Уравнение 3:
4,2*(3-4y)-2*(2,3y-2)=3,6y-3,4
12,6-16,8у-4,6+4=3,6у-3,4
-3,6у-16,8у=-12,6+4,6-4-3,4
-20,4у=-15,4
у=-15,4:(-20,4)
у=примерно 0,75
1. 3×(x-7)-6×(2x+5) = 2×(3x-1)+11
3x-21-12x-30 = 6x-2+11
3x-12x-6x = -2+11+21+30
-15x = 60
x = -4
2. -4×(x+5)+6x = 22-10x
-4x-20+6x = 22-10x
-4x+6x+10x = 22+20
12x = 42
x = 3,5
3. 4,2×(3-4y)-2×(2,3y-2) = 3,6y-3,4
12,6-16.8y-4.6y+4 = 3.6y-3.4
-16.8y-4.6y-3.6y = -3.4-12.6-4
-25y = -20
y = 0.8
...
Пошаговое объяснение:
Уравнение 1:
3*(x-7)-6*(2x+5)=2*(3x-1)+11
3х-21-12х-30=6х-2+11
3х-12х-6х=21+30-2+11
-15х=60
х=60:(-15)
х=-4
Уравнение 2:
-4*(x+5)+6x=22-10x
-4х-20+6х=22-10х
-4х+6х+10х=22+20
12х=42
х=42:12
х=3,5
Уравнение 3:
4,2*(3-4y)-2*(2,3y-2)=3,6y-3,4
12,6-16,8у-4,6+4=3,6у-3,4
-3,6у-16,8у=-12,6+4,6-4-3,4
-20,4у=-15,4
у=-15,4:(-20,4)
у=примерно 0,75
1. 3×(x-7)-6×(2x+5) = 2×(3x-1)+11
3x-21-12x-30 = 6x-2+11
3x-12x-6x = -2+11+21+30
-15x = 60
x = -4
2. -4×(x+5)+6x = 22-10x
-4x-20+6x = 22-10x
-4x+6x+10x = 22+20
12x = 42
x = 3,5
3. 4,2×(3-4y)-2×(2,3y-2) = 3,6y-3,4
12,6-16.8y-4.6y+4 = 3.6y-3.4
-16.8y-4.6y-3.6y = -3.4-12.6-4
-25y = -20
y = 0.8